OCCURRENCE OF COLIFORM BACTERIUM IN BOREHOLES WATER - MUHAMMAD, KABIRU; HALIMAT, SHUAIBU EBILOMA; MOHAMMED, SULAIMAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
To probe the quality of borehole water samples in Gombe Metropolis, water samples were collected from three wards including Pantami (ward A), Tudun Wada (ward B) and Jekada Fari (ward C). Physico-chemical and microbial analysis towards determining the quality of the water compared with Nigeria Standard for Drinking Water Quality (NSDWQ) and the World Health Organization (WHO) standard for were made. The mean values for temperature, pH, conductivity, total dissolved solids (TDS), hardness and chloride in the water sample were within the acceptable range of NSDWQ, except for turbidity and alkalinity. The water alkalinity was different across the wards and above the standards; A= 159.83 mg/L, B= 201.33 mg/L and C= 247.33 mg/L. Enterobacter aerogenes was the detected coliform in the water samples. Most of the physicochemical and microbial analyses conducted on the water samples were in accordance with the standard procedures. Thus, as a preventive measure to control the health threat associated with consumption of turbidity and alkaline water, the borehole water samples should only be used for bathing and washing. As well, the public should be provided with alternative water source for drinking and cooking purposes.